Follow up of civil society to the Quebec Action Plan: Report of Trinidad and Tobago: Freedom of Expression - (:unkn) unknown (My University, 2016)
Freedom of the press and freedom of expression are basic rights enshrined in the Trinidad and Tobago Constitution. Trinidad and Tobago has signed international treaties and agreements related to freedom of expression, including the United Nations’ Universal Declaration of Human Rights, the Declaration of Chapultepec, and the OAS Declaration, along with specific documents such as the International Covenant on Civil and Political Rights, and the Inter-American Convention on Human Rights.